2014
DOI: 10.4103/0971-4065.134089
|View full text |Cite
|
Sign up to set email alerts
|

Current concepts in C3 glomerulopathy

Abstract: Complement component 3 glomerulopathy (C3G) is a recently defined entity comprising of dense deposit disease and C3 glomerulonephritis. The key histological feature is the presence of isolated C3 deposits without immunoglobulins. Often masqueradng as some of the common glomerulonephritides this is a prototype disorder occurring from dysregulated alternate complement pathway with recently identified genetic defects and autoantibodies. We review the pathophysiology, clinical features, and diagnostic and treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 61 publications
(85 reference statements)
1
10
0
Order By: Relevance
“…C3 glomerulopathy (C3G) is an emerging kidney disease caused by dysregulation of the alternative complement pathway [ 1 5 ]. The characteristic pathology of this disease is glomerular depositions of dominant C3 with absent or weak immunoglobulins [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…C3 glomerulopathy (C3G) is an emerging kidney disease caused by dysregulation of the alternative complement pathway [ 1 5 ]. The characteristic pathology of this disease is glomerular depositions of dominant C3 with absent or weak immunoglobulins [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Given that C3G is defined by predominant glomerular C3 deposition (two orders greater than immunoglobulins), other glomerulonephritis types, particularly those that are immune complex-mediated, occasionally fit this criterion, too. Table 1 summarizes the clinical and histopathological features of DDD [ 5 , 32 , 46 , 52 – 56 ], C3GN [ 5 , 32 , 46 , 52 , 57 ], and PIGN [ 52 , 58 61 ].…”
Section: Introductionmentioning
confidence: 99%
“…The time to allograft recurrence in the two reported patients varies widely (in patient C3GN1 disease repalsed after 3 years, and in patient C3GN3 after 3 months), which is in line with previous reports [ 12 ]. Rituximab has been discussed as a treatment option in autoantibody positive transplant recurrent C3G [ 46 ]. In our study (patient C3GN1 ), it did not affect disease progression and a previous report showed poor outcome [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…C3NeF is prevalent in 50%-80% C3G patients[ 27 ]. Other autoantibodies have also been found ( e.g ., autoantibodies against factor B[ 28 ], CFH[ 29 , 30 ] and C3 convertase)[ 28 ].…”
Section: Clinical Presentationmentioning
confidence: 99%
“…There is no documented relation between mode of presentation, C3 serum levels, or C3NeF levels and C3GN recurrence[ 48 ]. The only trustworthy risk factor correlated with C3 recurrence is the presence of heavy proteinuria, with two thirds of C3 patients showing vulnerability to recurrence and a high incidence of graft loss[ 5 , 7 , 27 ]. All the available data about recurrence are based on case series, with the largest by Zand et al[ 7 ] that failed to reveal robust evidence of recurrence risk.…”
Section: Clinical Presentationmentioning
confidence: 99%